Pengaruh Mekanisme Good Corporate Governance pada Pengungkapan Tanggung Jawab Sosial Perusahaan Yang Tergabung Dalam Indeks Kompas 100. - Yuliani Yuliani (At-Tadbir : jurnal ilmiah manajemen, 2019)
The purpose of this study was to analyze the effect, good corporate governance mechanism through the composition of the independent board, independent audit committee composition and public ownership, on the disclosure of social responsibility (CSRI). This study also uses a variable sized firms, leverage and profitability as the control variables. The population used a company registered in the Kompas Index 100 period in 2017. The sample was taken by purposive sampling method, and which meet the criteria of sample selection. The samples used were 81 companies. Data collected through secondary data in the form of annual reports published in the period 2017 Indonesian Stock Exchange in 2018. Statistical testing method using multiple linear regression analysis, the statistical test of hypothesis testing and statistical test t F. The results of the analysis based on the use of all the independent variables and the control variables show that only the composition of the independent board and size significantly influence the company's CSR disclosure. Key words: Corporate Social Responsibility; Good Corporate Governance Mechanism; Company Size, Leverage, Profitability